Leveraging ICT innovations to support farmers and farmers’ organisations - Boyera, Stéphane; Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2017)
The data revolution is helping us make better decisions in all areas of our lives, and farmers are no exception. However, the smallholder farmer is being left behind as more data applications are developed for commercial farming. There is a need to better empower smallholder farmers to leverage information and communications technology (ICT) innovations for greater productivity and efficiency.